1999
DOI: 10.1002/(sici)1522-2594(199906)41:6<1269::aid-mrm26>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance diffusion imaging of the human cervical spinal cord in vivo

Abstract: Knowledge of water diffusion characteristics within the human spinal cord may provide important information about the structural nature of spinal cord pathology. However, the sensitivity of diffusion imaging methods to motion and the requirement for high in‐plane resolution has hitherto restricted study of spinal cord diffusion to excised samples. The first diffusion images of the human cervical spinal cord in vivo are presented using a navigated pulsed‐gradient spin‐echo sequence. Anisotropic diffusion in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
68
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 26 publications
7
68
1
Order By: Relevance
“…Water molecules, due to the limitation of the myelin sheath, moved rapidly along the white matter fiber tract but slowly along other directions. Diffusion anisotropy in the white matter of spinal cord was also confirmed in vivo by animal experiments in many literatures [5,7,10,11].…”
Section: Discussionmentioning
confidence: 58%
“…Water molecules, due to the limitation of the myelin sheath, moved rapidly along the white matter fiber tract but slowly along other directions. Diffusion anisotropy in the white matter of spinal cord was also confirmed in vivo by animal experiments in many literatures [5,7,10,11].…”
Section: Discussionmentioning
confidence: 58%
“…17 This paper described the use of a navigated, cardiac-gated diffusion sensitised spin-echo method which produced sagittal ADC maps of the spinal cord with an in-plane resolution of 0.94 mm and slice thickness of 5 mm in 15 min for two directions of diffusion sensitisation. Figure 1(a) and (b) shows ADC maps of the cervical spine sensitized to diffusion in the superior-inferior (SI) direction along the cord (ADC SI ) and anterior-posterior (AP) direction (ADC AP ) perpendicular to the cord, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…For example, diffusion changes in the spinal cord have been reported after spinal artery stroke, 1 multiple sclerosis, 2 cervical spondylotic myelopathy, 3 spinal cord compression, 4 acute spinal cord injury, 5 and chronic spinal cord injury, 6,7 yet detailed baseline data with use of common imaging sequences are lacking for comparison. Some diffusion measurements have been documented in targeted regions of the neurologically intact human spinal cord, [8][9][10][11][12] and these values have been used for comparison to pathologic conditions; however, a comprehensive study of diffusion parameters throughout the entire spinal cord has not been reported. As a result, the primary purpose of this study was to characterize the normative diffusion values of the entire human spinal cord with use of a clinically available pulse sequence for comparison with pathologic conditions and new pulse sequence designs.…”
mentioning
confidence: 99%
“…Unfortunately, the main alternative to EPI, pulsed-gradient, spin-echo DTI, is highly sensitive to motion and has very long imaging times, requiring approximately 15 minutes to image a single diffusion axis. 9 A few pulse sequences focus on a compromise between these 2 methods, including line scan diffusion imaging, 13 multishot echo-planar imaging, 10 and fast single-shot EPI with use of sensitivitiy encoding (SENSE).…”
mentioning
confidence: 99%